2021
DOI: 10.3390/children8010051
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Dominant Hand and the Occurrence of the Supracondylar Humerus Fracture in Pediatric Orthopedics

Abstract: It is known that during a fall, a child would rather protect their dominant hand by using the non-dominant one, although the role of handedness in upper limb fractures has not been studied in-depth. We carried out a retrospective, cross-sectional cohort study, including pediatric patients who presented to the emergency room with a supracondylar humerus fracture following an injury by falling from the same height. In total, 245 patients were selected and grouped according to age. In the 1–3 years group, no stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…In contrast, OI results in impaired bone mineralization, allowing for fractures after much less imparted energy. We postulate that many OI HWFs occur in the dominant hand as a result of injury during daily use, aligning with the current literature on handedness 11,12 …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In contrast, OI results in impaired bone mineralization, allowing for fractures after much less imparted energy. We postulate that many OI HWFs occur in the dominant hand as a result of injury during daily use, aligning with the current literature on handedness 11,12 …”
Section: Discussionsupporting
confidence: 74%
“…We postulate that many OI HWFs occur in the dominant hand as a result of injury during daily use, aligning with the current literature on handedness. 11,12 OI HWFs present commonly as transverse fractures, with buckle and avulsion fractures less common in the OI population. The differences in observed fracture morphology may be due to the bone quality in patients with OI; however, prior studies have reported radiographically normal appearance of nonfractured hand and wrist bones in patients with OI.…”
Section: Discussionmentioning
confidence: 99%
“…It is most common in children aged 5 to 7 years old, with the non-dominant hand more frequently involved. No substantial difference was observed between boys and girls [1][2][3][4].…”
Section: Introductionmentioning
confidence: 73%
“…For pain intensity assessment, we used the Numerical Rating Scale for patients older than ten years, and the Wong-Baker Faces Pain Rating Scale/Faces Pain Scale for pediatric patients between the ages of 3 and 10 [9, [13][14][15][16][17].…”
Section: Methodsmentioning
confidence: 99%